2015
DOI: 10.1016/j.ijgo.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Risk of invasive cancer among women visually screened and colposcopy triaged by trained nurses in rural south India

Abstract: The high risk of cancer among women without colposcopic abnormalities who tested positive by VIA suggested that screening without triage is potentially effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…12 In a randomized controlled trial in India, the risk of invasive cancer among VIA-positive women with apparently normal colposcopy and histopathology during 12 years of follow-up was much higher than that of VIA-negative women (hazard ratio 6.5; 95% CI, 1.6-27.1). 13 The risk was similar to that observed in VIA-positive women with colposcopically detected abnormalities who did not undergo biopsy or treatment, thus demonstrating the futility of colposcopy in this scenario.…”
Section: Referral To Confirmatory Colposcopysupporting
confidence: 66%
See 1 more Smart Citation
“…12 In a randomized controlled trial in India, the risk of invasive cancer among VIA-positive women with apparently normal colposcopy and histopathology during 12 years of follow-up was much higher than that of VIA-negative women (hazard ratio 6.5; 95% CI, 1.6-27.1). 13 The risk was similar to that observed in VIA-positive women with colposcopically detected abnormalities who did not undergo biopsy or treatment, thus demonstrating the futility of colposcopy in this scenario.…”
Section: Referral To Confirmatory Colposcopysupporting
confidence: 66%
“…In the atypical cells of undetermined significance, low‐grade squamous intraepithelial lesion (ASCUS‐LSIL) Triage Study (ALTS), the sensitivity of baseline colposcopy for the subsequent detection of CIN 3+ was only 53% . In a randomized controlled trial in India, the risk of invasive cancer among VIA‐positive women with apparently normal colposcopy and histopathology during 12 years of follow‐up was much higher than that of VIA‐negative women (hazard ratio 6.5; 95% CI, 1.6–27.1) . The risk was similar to that observed in VIA‐positive women with colposcopically detected abnormalities who did not undergo biopsy or treatment, thus demonstrating the futility of colposcopy in this scenario.…”
Section: Referral To Confirmatory Colposcopymentioning
confidence: 75%
“…By implication, the Musoma, Bukumbi, and Shinyanga districts will have to be targeted with greater screening intensity. A disappointing finding is that none of these determinants is known to be favourably associated with the uptake of cervical screening in sub-Saharan Africa (as is the case for contraceptive use, for example) (Thulaseedharan et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study from India observed very low risk of developing cervical cancer in women with histopathology‐proved CIN1 after colposcopy . However, the women in the study were screened with visual inspection after acetic acid application (VIA) and the HPV status of the women at baseline was unknown.…”
mentioning
confidence: 99%